Does Europe need a comprehensive energy policy? - Christian Egenhofer; Arno Behrens; Richard S. J. Tol; Michel Berthélemy; François Lévêque; Jaap C. Jansen (Intereconomics, 2011)
The nuclear meltdown in Fukushima has given renewed momentum to the anti-nuclear power movement across Europe. However, the degree of momentum varies greatly from country to country, and considering the geographically widespread consequences of a nuclear accident, it hardly appears optimal for one country to ban nuclear power while multiple nuclear power plants are still active in neighbouring countries. Even beyond the nuclear power dilemma, the economic and political externalities associated with energy policy are diffi cult to overstate. The contributions to this Forum look into the benefits expected from a comprehensive common energy policy for Europe and the problems which establishing such a policy would involve.
Keywords: 330